Interaction of THP-1 Monocytes with Conidia and Hyphae of Different Curvularia Strains - Tóth, Eszter Judit (Front Immunol, 2017)
Interaction of the human monocytic cell line, THP-1 with clinical isolates of three Curvularia species were examined. Members of this filamentous fungal genus can cause deep mycoses emerging in both immunocompromised and immunocompetent patients. It was found that monocytes reacted only to the hyphal form of Curvularia lunata. Cells attached to the germ tubes and hyphae and production of elevated levels of interleukin (IL)-8 and IL-10 and a low level of TNF-α were measured. At the same time, monocytes failed to produce IL-6. This monocytic response, especially with the induction of the anti-inflammatory IL-10, correlates well to the observation that C. lunata frequently cause chronic infections even in immunocompetent persons. Despite the attachment to the hyphae, monocytes could not reduce the viability of the fungus and the significant decrease in the relative transcript level of HLA-DRA assumes the lack of antigen presentation of the fungus by this cell type. C. spicifera and C. hawaiiensis failed to induce the gathering of the cells or the production of any analyzed cytokines. Monocytes did not recognize conidia of Curvularia species, even when melanin was lacking in their cell wall.